Cast aluminum-lithium alloy as well as preparation method and application thereof

By optimizing the composition and process of aluminum-lithium alloys, an aluminum-lithium alloy with specific precipitation phases and intermetallic compound phases is formed, which solves the problem of softening of traditional aluminum-lithium alloys under high temperature conditions and achieves better high temperature mechanics Performance and comprehensive mechanical properties.

CN119464847APending Publication Date: 2025-02-18JIANGSU XCMG CONSTRUCTION MACHINERY RESEARCH INSTITUTE LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411588299.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Traditional cast aluminum-lithium alloys will soften at 150°C and cannot be used stably under high temperature conditions, which limits its application in complex structural castings.

Method used

By optimizing the composition design and process of aluminum-lithium alloys, 2.0% to 3.0% Li, 0.8% to 1.2% Cu, 0.1% to 0.2% Zr, 0.5% to 1.8% Mg, 0.8% to 3.0 were used. % Si, 0.15% to 0.55% rare earth elements and ≤0.40% Fe, with the balance of Al, two-stage solution treatment, quenching treatment and two-stage aging treatment to form a rod-shaped Mg2Si precipitation phase and distribution along grain boundaries. AlSiLi intermetallic compound phase aluminum-lithium alloy.

Benefits of technology

It significantly improves the high-temperature mechanical properties of aluminum-lithium alloys, delays the high-temperature softening behavior, and enhances its comprehensive mechanical properties under room temperature and high temperature conditions. It is suitable for lightweight and heat-resistant applications of complex structural castings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464847A_ABST
    Figure CN119464847A_ABST
Patent Text Reader

Abstract

The invention provides a cast aluminum-lithium alloy and a preparation method and application thereof, and the cast aluminum-lithium alloy comprises the following components in percentage by mass: 2.0%-3.0% of Li, 0.8%-1.2% of Cu, 0.1%-0.2% of Zr, 0.5%-1.8% of Mg, 0.8%-3.0% of Si, 0.15%-0.55% of rare earth element, less than or equal to 0.40% of Fe and the balance of Al; the rare earth elements comprise Sc and / or Er. The cast aluminum-lithium alloy provided by the invention has improved heat resistance, has excellent comprehensive mechanical properties under the service conditions of room temperature and high temperature, and can be applied to the fields of engineering machinery and the like as a heat-resistant lightweight structural member.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of nonferrous metallurgy, and specifically relates to a cast aluminum-lithium alloy and a preparation method and application thereof. Background Art

[0002] With the development of construction machinery towards miniaturization, lightweight and greening, the proportion of aluminum alloy used in the field of construction machinery and the quality requirements have been greatly improved, and the demand for lightweight, heat-resistant, complex structure thin-walled castings has become increasingly strong.

[0003] Aluminum-lithium alloy is a typical lightweight structural material with the characteristics of low density, high elastic modulus, specific strength, fatigue strength, etc. Using it as a substitute for traditional high-strength aluminum alloy can reduce the structural mass by 10% to 20% and increase the stiffness by 15% to 20%. Among them, cast aluminum-lithium alloy is an ideal new generation of lightweight room temperature structural material due to its light weight, excellent comprehensive mechanical properties and good filling capacity. However, traditional cast aluminum-lithium alloy will soften rapidly at 150°C, which limits the stable service of cast aluminum-lithium alloy under high temperature conditions. Therefore, the development of a new generation of lightweight heat-resistant cast aluminum alloy can achieve the lightweight of complex structural castings, reduce the energy consumption of equipment / equipment, and has important economic and environmental benefits.

[0004] Generally speaking, the δ' phase (Al3Li) is usually used as the main strengthening phase of cast aluminum-lithium alloys. The δ' phase precipitates from the supersaturated solid solution in the form of a metastable phase during the aging treatment stage. Through this precipitation strengthening mechanism, the cast aluminum-lithium alloy can obtain significant hardening and strengthening effects after solution aging heat treatment. However, due to the coherent relationship between the δ' phase and the aluminum-lithium alloy matrix, coplanar slip is prone to occur, causing dislocations to accumulate at the intersection of the slip plane and the grain boundary, causing stress concentration, resulting in a decrease in the room temperature toughness of the alloy; at the same time, the δ' phase is a metastable phase and is very easy to dissolve back at high temperatures. The alloy matrix also has a serious high-temperature softening phenomenon, which makes the aluminum-lithium alloy cannot be used in high-temperature environments. Therefore, it is necessary to explore the improvement of the high-temperature mechanical properties of cast aluminum-lithium alloys through composition design and process adjustment. Summary of the invention

[0005] The present invention provides a cast aluminum-lithium alloy and a preparation method and application thereof, so as to slow down the high-temperature softening behavior of the cast aluminum-lithium alloy, improve the heat resistance, and thus improve the comprehensive mechanical properties of the cast aluminum-lithium alloy under room temperature and high-temperature service conditions.

[0006] The first aspect of the present application provides a cast aluminum-lithium alloy, which includes, by mass percentage, 2.0% to 3.0% Li, 0.8% to 1.2% Cu, 0.1% to 0.2% Zr, 0.5% to 1.8% Mg, 0.8% to 3.0% Si, 0.15% to 0.55% rare earth elements, ≤0.40% Fe, and the balance is Al; the rare earth elements include Sc and / or Er.

[0007] In any embodiment of the first aspect, based on the total weight of the cast aluminum-lithium alloy, the rare earth elements include 0.15% to 0.30% Sc, 0.35% to 0.55% Er, or a combination of Sc and Er, and when the rare earth elements include a combination of Sc and Er, the mass percentage of Sc is 0.10% to 0.15%, and the mass percentage of Er is 0.15% to 0.25%.

[0008] In any embodiment of the first aspect, the mass fraction ratio Mg / Si of the Mg element to the Si element in the cast aluminum-lithium alloy is 0.63 to 1.88.

[0009] In any embodiment of the first aspect, the cast aluminum-lithium alloy has a rod-shaped Mg2Si precipitate phase on the α-Al matrix phase.

[0010] In any embodiment of the first aspect, the cast aluminum-lithium alloy has an AlSiLi intermetallic compound phase distributed along the grain boundaries in a discontinuous or nearly continuous manner.

[0011] In any embodiment of the first aspect, the cast aluminum-lithium alloy satisfies one or more of the following characteristics: (1) at 25°C, the yield strength is 286-326 MPa, the tensile strength is 314-389 MPa and / or the elongation is 4.2%-14.7%; (2) at 200°C, the yield strength is 211-250 MPa, the tensile strength is 223-297 MPa and / or the elongation is 7.4%-13.9%; (3) at 300°C, the yield strength is 109-148 MPa, the tensile strength is 115-159 MPa and / or the elongation is 12.4%-17.3%.

[0012] The second aspect of the present application provides a method for preparing a cast aluminum-lithium alloy, the method comprising:

[0013] Step 1, smelting the alloy raw material to obtain aluminum liquid, and pouring the aluminum liquid to form an aluminum-lithium alloy blank, wherein the alloy raw material comprises, by mass percentage: 2.0% to 3.0% Li, 0.8% to 1.2% Cu, 0.1% to 0.2% Zr, 0.5% to 1.8% Mg, 0.8% to 3.0% Si, 0.15% to 0.55% rare earth elements, ≤0.40% Fe, and the balance is Al; the rare earth elements include Sc and / or Er;

[0014] Step 2: The aluminum-lithium alloy blank is subjected to a double-stage solution treatment, a quenching treatment and a double-stage aging treatment in sequence to obtain a cast aluminum-lithium alloy.

[0015] In any embodiment of the second aspect, the two-stage solution treatment comprises a first-stage solution treatment and a second-stage solution treatment performed sequentially, wherein the solution temperature T s1 500℃~520℃, solution time t s1 The second stage solid solution temperature is T s2 540℃~560℃, solution time t s2 It is 10 to 16 hours.

[0016] In any embodiment of the second aspect, the two-stage aging treatment includes a first-stage aging and a second-stage aging performed sequentially, and the aging temperature T of the first-stage aging is a1 150℃±3℃, aging time t a1 8 to 12 hours; the aging temperature of the second stage aging is T a2 175℃~190℃, aging time t a2 8 to 48 hours.

[0017] In any embodiment of the second aspect, the above-mentioned step one includes: smelting pure aluminum and an aluminum-based master alloy containing alloying elements at 750°C to 800°C to form an alloy melt, the alloying elements include one or more of Cu, Zr, Si, and rare earth elements, and the rare earth elements include Sc and / or Er; reducing the temperature to 720°C to 730°C, and pressing pure magnesium wrapped in aluminum foil and pure lithium wrapped in aluminum foil into the alloy melt under a protective atmosphere, and the protective atmosphere can be selected from nitrogen and / or argon; adjusting the temperature to 740°C to 750°C, degassing the alloy melt with a degassing agent, and standing to obtain aluminum liquid; pouring the aluminum liquid at 720°C±5°C to form an aluminum-lithium alloy billet.

[0018] In any embodiment of the second aspect, the entire process of step 1 is carried out under a protective gas atmosphere, and the protective gas can be argon gas, and further can be argon gas with a purity of not less than 99.99% and a flow rate of 0.5m 3 / h~1.5m 3 / h of argon.

[0019] In any embodiment of the second aspect, step 1 satisfies one or more of the following conditions:

[0020] 1) The degassing agent is selected from any one or more of C2Cl6, CCl4, and Mg3N2, preferably C2Cl6, and more preferably, C2Cl6 is 0.45% to 0.8% of the total mass of the alloy raw material; 2) The standing time is 10 to 15 minutes.

[0021] In any embodiment of the second aspect, the preparation method further comprises pre-treating the alloy raw material, and the pre-treating the alloy raw material comprises: removing surface oxide scale and performing anti-oxidation treatment on pure aluminum and aluminum-based master alloy containing alloying elements.

[0022] In any embodiment of the second aspect, during the quenching treatment, the temperature is rapidly reduced from 540° C. to 560° C. to 25° C., and the quenching medium is preferably brine or water at room temperature.

[0023] The third aspect of the present application provides a heat-resistant lightweight structural part, which includes an aluminum-lithium alloy. The aluminum-lithium alloy is any one of the cast aluminum-lithium alloys in the first aspect, or the aluminum-lithium alloy is obtained by any one of the preparation methods in the second aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 The SEM images of the cast aluminum-lithium alloys in Examples 1-3 of the present application, from left to right are the SEM images of the cast aluminum-lithium alloys of Example 1, Example 2, and Example 3;

[0026] Figure 2 The SEM images of the T6 aluminum-lithium alloys in Examples 1-3 of the present application, from left to right are the SEM images of the T6 aluminum-lithium alloys of Example 1, Example 2, and Example 3;

[0027] Figure 3 TEM images of T6 aluminum-lithium alloys in Examples 1-3 of the present application, from left to right are TEM images of T6 aluminum-lithium alloys of Example 1, Example 2, and Example 3;

[0028] Figure 4 This is a TEM image of the T6 aluminum-lithium alloy in Example 3 of the present application. DETAILED DESCRIPTION

[0029] The following embodiments further describe the implementation of the present application in detail. The detailed description of the following embodiments is used to illustrate the principle of the present application, but cannot be used to limit the scope of the present application, that is, the present application is not limited to the described embodiments.

[0030] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0031] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0032] As analyzed in the background technology of this application, conventional cast aluminum-lithium alloys will soften rapidly at 150°C and cannot achieve stable service at high temperatures of 200°C to 300°C. In this context, this application provides a cast aluminum-lithium alloy and a preparation method thereof, as well as a heat-resistant lightweight structural part comprising the aluminum-lithium alloy.

[0033] The first embodiment of the present application provides a cast aluminum-lithium alloy, which includes, by mass percentage, 2.0% to 3.0% Li, 0.8% to 1.2% Cu, 0.1% to 0.2% Zr, 0.5% to 1.8% Mg, 0.8% to 3.0% Si, 0.15% to 0.55% rare earth elements, ≤0.40% Fe, and the balance is Al; the rare earth elements include Sc and / or Er.

[0034] The cast aluminum-lithium alloy in the present application is a lightweight, heat-resistant cast aluminum-lithium alloy, which has both high strength and plasticity at room temperature and excellent high-temperature mechanical properties, and can be used in key core components in the field of engineering machinery such as pistons and cylinders.

[0035] The cast aluminum-lithium alloy of the present application belongs to a cast aluminum alloy. Compared with the deformed aluminum-lithium alloy, the cast aluminum-lithium alloy can have a higher Li content, and the mass content of Li in the cast aluminum-lithium alloy can be up to 4.2%. Due to the addition of Li element, the aluminum-lithium alloy has a lower density and a higher specific strength.

[0036] The Fe element is an impurity, which is brought into the alloy melt by commercially pure aluminum ingots and easily forms harmful phases in the aluminum alloy. Therefore, the allowable Fe content by mass should not be higher than 0.40%.

[0037] In the above-mentioned cast aluminum-lithium alloy, other alloying elements except Fe can play the following roles within a limited range:

[0038] Cu and Mg are the main alloying elements in cast aluminum-lithium alloys. Cu can significantly improve the strength and toughness of aluminum-lithium alloys. An appropriate amount of Cu element can weaken the local strain of the alloy and form a lath-shaped precipitation strengthening phase T1 phase (Al2CuLi) together with Al and Li elements. The T1 phase has a strong strengthening effect and is beneficial to improving the tensile strength and yield strength of the alloy.

[0039] Mg has a large solid solubility in Al, which can produce a solid solution strengthening effect, strengthening the low-strength precipitation-free zone (PFZ) located at the grain boundary, effectively alleviating the propagation of microcracks along the precipitation-free zone, reducing the probability of intergranular fracture, and helping to improve the strength and stiffness of the alloy.

[0040] Adding Cu and Mg at the same time can promote the formation of the needle-shaped metastable S' phase (Al2CuMg). Both the S' phase and the T1 phase are difficult to be cut by dislocations, so they can effectively disperse the slip, improve the deformation uniformity of the alloy, and thus improve the strength and plasticity of the aluminum-lithium alloy.

[0041] Zr can form a rod-shaped metastable β' phase (Al3Zr) with Al in Al. Zr atoms have a large binding energy with vacancies and can combine with vacancies before Li during the solidification of the alloy, thereby inhibiting the precipitation of the δ' phase. At the same time, the δ' phase nucleates and grows at the metastable β' phase interface to form a composite structure phase with higher hardness, which can increase the mismatch between the δ' phase and the matrix, effectively inhibit coplanar slip, and improve the plasticity of aluminum-lithium alloys.

[0042] Sc and Er have similar effects, both of which can refine grains. In comparison, Sc is better than Er in grain refinement, and Er is cheaper and more economical than Sc. In addition, by adding rare earth elements M (M is Sc and / or Er) and Zr at the same time, after solution aging treatment, a ternary coherent phase Al3 (M 1-x Zr x ), which has a core-shell structure and presents a nano-sized dispersed distribution, achieving dispersion strengthening, thereby improving the mechanical stability of the alloy at room temperature and high temperature.

[0043] In the present application, Si element is an added functional element. On the one hand, Si element forms Mg2Si precipitation phase with Mg element. Mg2Si has a high melting point and high microhardness, which is beneficial to improve the strength and hardness of the alloy and can effectively resist softening and instability under high temperature conditions. On the other hand, it can form AlSiLi intermetallic compounds. When AlSiLi intermetallic compounds are distributed along grain boundaries, they can play a role in skeleton strengthening, inhibit dislocation movement, and thus improve the strength of the alloy.

[0044] In the present application, the rare earth elements Sc and Er have similar effects, both of which can refine the grains, significantly improve the strength and plasticity of the alloy, and improve the thermal stability of the cast aluminum-lithium alloy. At the same time, the rare earth elements Sc and Er can form a precipitation strengthening phase after solution aging heat treatment, which is beneficial to the strength of the alloy. The addition of rare earth elements is also beneficial to the fluidity and purity of the alloy melt during the smelting process. In some embodiments, in order to optimize the effects of Sc and Er, the rare earth elements include 0.15% to 0.30% Sc, 0.35% to 0.55% Er, or a combination of Sc and Er, and when the rare earth elements include a combination of Sc and Er, the mass percentage of Sc is 0.10% to 0.15%, and the mass percentage of Er is 0.15% to 0.25%. For example, calculated by mass percentage, the rare earth elements may be 0.15% Sc, 0.18% Sc, 0.25% Sc, and 0.3% Sc; for another example, calculated by mass percentage, the rare earth elements may be 0.35% Er, 0.40% Er, 0.45% Er, 0.50% Er, and 0.55% Er; for another example, calculated by mass percentage, the rare earth elements may be 0.1% Sc and 0.15% Er, 0.1% Sc and 0.20% Er, 0.15% Sc and 0.15% Er, 0.15% Sc and 0.25% Er.

[0045] In some embodiments, the mass fraction ratio Mg / Si of Mg element to Si element in the cast aluminum-lithium alloy is 0.83 to 1.88. When Mg / Si is within the above range, a relatively uniformly dispersed Mg2Si strengthening phase can be formed, and strength and plasticity can achieve a better balance, which is beneficial to improve crack resistance and further improve room temperature and high temperature comprehensive mechanical properties. By way of example but not limitation, the mass fraction ratio Mg / Si of Mg element to Si element in the aluminum-lithium alloy can be 0.9, 1.0, 1.1, 1.2, 1.5, 1.7, 1.8. If Mg / Si is higher than 1.88, the size of the Mg2Si precipitated phase in the alloy matrix is ​​relatively large, and the effect of improving the strength and hardness of the alloy is relatively limited; if Mg / Si is lower than 0.83, the amount of Si added is too much, and a large-sized AlSiLi primary phase is easily formed, resulting in stress concentration at the interface between the alloy matrix and the large-sized AlSiLi phase, affecting the strength-plasticity of the alloy.

[0046] In some embodiments, the cast aluminum-lithium alloy has a rod-shaped Mg2Si precipitated phase on the α-Al matrix phase. The Mg2Si phase is an aging-strengthened phase precipitated from the α-Al matrix after aging treatment, has a high hardness, can hinder dislocation movement, and improve the yield strength and tensile strength of the alloy. In addition, the Mg2Si phase has good thermal stability and can still maintain its strengthening effect at higher temperatures, which is conducive to improving the high-temperature performance of the alloy.

[0047] The density of AlSiLi intermetallic compound is about 2g / cm 3 , which is lower than the density of Al, belongs to a low-density strengthening phase, has good heat resistance and high hardness. In some embodiments, the aluminum-lithium alloy has an AlSiLi intermetallic compound phase distributed along the grain boundary in a discontinuous or nearly continuous manner. The AlSiLi intermetallic compound phase can effectively inhibit the dislocation movement between grains, thereby improving the strength of the aluminum-lithium alloy and the high-temperature structural stability.

[0048] In some embodiments, the cast aluminum-lithium alloy satisfies one or more of the following characteristics: (1) at 25°C, the yield strength is 286-326 MPa, the tensile strength is 314-389 MPa and / or the elongation is 4.2%-14.7%; (2) at 200°C, the yield strength is 211-250 MPa, the tensile strength is 223-297 MPa and / or the elongation is 7.4%-13.9%; (3) at 300°C, the yield strength is 109-148 MPa, the tensile strength is 115-159 MPa and / or the elongation is 12.4%-17.3%.

[0049] The second embodiment of the present application provides a method for preparing a cast aluminum-lithium alloy, comprising: step one, smelting an alloy raw material to obtain aluminum liquid, and pouring the aluminum liquid to form an aluminum-lithium alloy blank, wherein the alloy raw material comprises, by mass percentage: 2.5% Li, 1.0% Cu, 0.15% Zr, 0.5% to 1.8% Mg, 0.8% to 3.0% Si, 0.15% to 0.55% rare earth elements, ≤0.40% Fe, and the balance is Al; the rare earth elements include Sc and / or Er; step two, the aluminum-lithium alloy blank is subjected to a two-stage solid solution treatment, a quenching treatment, and a two-stage aging treatment in sequence to obtain a cast aluminum-lithium alloy.

[0050] It should be pointed out that both pure magnesium and pure lithium have a certain degree of burn-out during the smelting stage. The mass percentage of Mg and Li in the above alloy raw materials does not take the burn-out amount into account. Usually, the burn-out amount of pure magnesium during the smelting process is about 10%, and the burn-out amount of pure lithium is about 20%. The burn-out amount only needs to be considered during the actual mixing of ingredients.

[0051] The preparation method of cast aluminum-lithium alloy provided in this application is improved and designed for alloying element composition and heat treatment process, and the composite microalloying is combined with two-stage solid solution and two-stage aging treatment process, which effectively refines the matrix structure of aluminum-lithium alloy, precipitates Mg2Si precipitation strengthening phase in the matrix, and promotes the precipitation of heat-resistant Si-rich phase (AlSiLi intermetallic compound phase, hereinafter referred to as AlSiLi phase) along the grain boundary, and part of AlSiLi phase can form a nearly continuous network distribution, forming a "skeleton" of the strengthened alloy, which hinders the movement of dislocations between grains. Thus, the strength-plasticity of aluminum-lithium alloy is synergistically improved, and the comprehensive mechanical properties of aluminum-lithium alloy and deformation resistance under high temperature service conditions are enhanced, and it has excellent deformation resistance under high temperature service conditions of 200℃ to 300℃.

[0052] In some embodiments, the preparation method of the above-mentioned cast aluminum-lithium alloy further includes pre-treating the alloy raw material, and the pre-treating of the alloy raw material includes: removing the surface oxide scale and anti-oxidation treatment of pure aluminum and aluminum-based master alloys containing alloying elements. Among them, the aluminum-based master alloy containing alloying elements includes one or more of Al-50Cu master alloy, Al-4Zr master alloy, Al-12Si master alloy and Al-10Sc master alloy, and other commercially available aluminum-based master alloys containing alloying elements can also be selected. By way of example but not limitation, the surface oxide scale is removed by mechanical grinding, and the alloy raw material block is placed in a dry environment to prevent surface oxidation.

[0053] The smelting process of the present application can refer to the smelting process in the conventional aluminum-lithium alloy casting process. In some embodiments, step one includes: smelting pure aluminum and an aluminum-based master alloy containing alloying elements at 750°C to 800°C to form an alloy melt, the alloying elements include one or more of Cu, Zr, Si, and rare earth elements, and the rare earth elements include Sc and / or Er; reducing the temperature to 720°C to 730°C, and pressing pure magnesium wrapped in aluminum foil and pure lithium wrapped in aluminum foil into the alloy melt under a protective atmosphere, and the protective atmosphere can be selected from nitrogen and / or argon; adjusting the temperature to 740°C to 750°C, degassing the alloy melt with a degassing agent, and standing to obtain aluminum liquid; pouring the aluminum liquid at 720°C±5°C to form an aluminum-lithium alloy billet.

[0054] Smelting at the above-mentioned temperature of 750°C to 800°C can achieve rapid melting of metal elements. Adding magnesium, aluminum and lithium after melting to form a melt and cooling can reduce the burn-off of lithium and magnesium elements. At the same time, wrapping pure magnesium and pure lithium with aluminum foil further reduces the burn-off of lithium and magnesium in the process.

[0055] In some embodiments, pure magnesium and pure lithium particles wrapped in aluminum foil may be pressed into the melt in batches using a graphite cover under a protective atmosphere, thereby providing better protection for Mg and Li, which are chemically more active, easily oxidized, and easily ablated.

[0056] In some embodiments, the entire process of step 1 is carried out under a protective gas atmosphere. The use of inert gas protection smelting can replace the traditional protection method of covering the surface of the molten pool with flux, which is conducive to reducing casting defects such as non-metallic inclusions, gas, slag inclusions, and improving casting quality. Further, in some embodiments, the protective gas can be argon gas, and further can be argon gas with a purity of not less than 99.99% and a flow rate of 0.5m 3 / h~1.5m 3 / h of argon gas, providing adequate protection while avoiding excessive flow that would inhale air from the environment.

[0057] In some embodiments, step 1 satisfies one or more of the following conditions: 1) the degasser is selected from any one or more of C2Cl6, CCl4, and Mg3N2, preferably C2Cl6, and more preferably, C2Cl6 is 0.6% of the total mass of the alloy raw material; 2) the standing time is 10 to 15 minutes. At 740°C to 750°C, the degasser (such as C2Cl6) decomposes to form bubbles, and the hydrogen dissolved in the aluminum liquid diffuses into the bubbles under pressure and precipitates as the bubbles float up. At the same time, the wetted oxidizing inclusions are adsorbed on the surface of the bubbles under the action of surface tension and are brought to the surface of the aluminum liquid to form scum. The degassing time depends on the quality of the alloy melt. When the alloy melt does not emit black smoke and no bubbles float on the surface of the alloy melt, the degassing can be terminated and the mixture can be left standing.

[0058] The microstructure of the cast aluminum-lithium alloy is as follows: Figure 1 As shown in the figure, through scanning electron microscopy morphology characterization, it can be seen that the alloy matrix has relatively coarse grains, the grain size and distribution are relatively uneven, and there is a discontinuous or nearly continuous distribution of AlSiLi phase along the grain boundary.

[0059] In some embodiments, the double-stage solution treatment includes a first-stage solution treatment and a second-stage solution treatment performed sequentially, and the solution temperature T of the first-stage solution treatment is s1 500℃~520℃, solution time t s1 The second stage solid solution temperature is T s2 540℃~560℃, solution time t s2The time required for the treatment is 10 to 16 hours. The first stage of solid solution can dissolve the low melting point eutectic phase into the matrix to prevent it from melting at high temperature; the second stage of solid solution can dissolve more intermetallic compounds into the matrix to improve the solid solution strengthening effect of the alloy. During the solid solution treatment, the AlSiLi phase distributed discontinuously or nearly continuously along the grain boundary will partially dissolve into the matrix phase to form a supersaturated solid solution.

[0060] In some embodiments, the temperature is rapidly reduced from 540°C to 560°C to 25°C (room temperature) during quenching, and the quenching medium is preferably salt water or water at room temperature. Through quenching, the solute atoms are retained in the alloy matrix in the shortest possible time to form a supersaturated solid solution, which is beneficial to improving the aging strengthening effect in the subsequent stage.

[0061] The main purpose of aging is to obtain a uniform and finely dispersed precipitated phase, thereby improving the strength of the alloy. In some embodiments, the double-stage aging treatment includes a first-stage aging and a second-stage aging performed sequentially, and the aging temperature of the first-stage aging is T a1 150℃±3℃, aging time t a1 8 to 12 hours; the aging temperature of the second stage aging is T a2 175℃~190℃, aging time t a2 8 to 48 hours. The present application adopts an aging treatment method of "low-temperature pre-aging + high-temperature re-aging". During the first stage of aging, a nanoscale and diffusely distributed solute atom segregation zone (GP zone) appears on the alloy matrix, followed by a series of metastable precipitation phases. Part of the primary phase AlSiLi in the aluminum-lithium alloy blank formed by the aforementioned casting is dissolved into the alloy matrix phase during the solid solution process. During the aging period, it is in the form of a precipitated phase with a spherical morphology. After the second stage of aging, the AlSiLi intermetallic compound still exists as a residual second phase at the grain boundary in a discontinuous or nearly continuous manner. At the same time, a large number of short rod-shaped Mg2Si phases (β phases) are precipitated on the alloy matrix, which can have a strengthening effect.

[0062] The third embodiment of the present application provides a heat-resistant lightweight structural part, which includes an aluminum-lithium alloy. The aluminum-lithium alloy here is any one of the cast aluminum-lithium alloys in the first embodiment, or the aluminum-lithium alloy here is obtained by any one of the preparation methods of the cast aluminum-lithium alloy in the second embodiment.

[0063] [Example]

[0064] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention, and further illustrate the beneficial effects of the present application through examples and comparative examples. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0065] In the following text, T6 aluminum-lithium alloy refers to the alloy state after the cast aluminum-lithium alloy billet is subjected to the heat treatment of "solid solution treatment + artificial aging".

[0066] Example 1

[0067] In terms of mass percentage, the base composition elements and contents of the cast aluminum-lithium alloy in this embodiment are: Li 2.5%, Cu 1.0%, Zr 0.15%, Mg 1.5%, Fe≤0.40%, and the balance is A1. The composite alloying scheme of this embodiment is to add 0.8% Si and 0.2% Sc.

[0068] Alloy melting and casting :

[0069] Add pure aluminum, Al-50Cu alloy, Al-4Zr, Al-12Si and Al-10Sc master alloy with good proportion into the crucible. The above alloy raw materials have been subjected to surface oxide skin removal and anti-oxidation treatment. Use a resistance furnace to raise the temperature to a range of 750°C to 800°C for smelting. After all the materials are melted, slag is removed to form an alloy melt.

[0070] The temperature is lowered to 720°C to 730°C, and pure magnesium and pure lithium pellets wrapped in aluminum foil are pressed into the alloy melt in batches using a graphite cover under the protection of high-purity argon gas, with a burnout amount of 10% for pure magnesium and 20% for pure lithium. After the pure magnesium and pure lithium pellets diffuse into the melt and stabilize, C2Cl6 is wrapped in aluminum foil and pressed into the alloy melt, and degassing is performed using C2Cl6 at 740°C to 750°C until the melt does not emit black smoke and bubbles float out of the melt, and the amount of C2Cl6 is 0.6% of the total mass of the alloy;

[0071] The alloy melt was allowed to stand for 15 minutes and then cast at 720° C. to form a cast aluminum-lithium alloy blank;

[0072] During the above smelting and casting process, argon gas with a purity of 99.99% was used to protect the alloy melt. During the smelting and casting process, the argon gas flow rate was 1m 3 / h;

[0073] Solution and aging treatment :

[0074] In a box-type resistance furnace, a two-stage solution treatment process is used to perform solution treatment on the aluminum-lithium alloy blank obtained above, wherein the solution temperature of the first stage solution is 500°C, the solution time is 4 hours, and the solution temperature of the second stage solution is 540°C, the solution time is 12 hours;

[0075] The aluminum-lithium alloy blank after the solid solution treatment is quenched, and the quenching medium is water at room temperature, and the temperature is reduced from 540° C. to 25° C. as quickly as possible;

[0076] The aluminum-lithium alloy billet after the quenching treatment is placed in a salt bath furnace for double-stage aging treatment. The aging temperature of the first stage is 150°C and the duration is 10 h. The aging temperature of the second stage is 190°C and the duration is 8 h. It is then naturally cooled to room temperature to obtain a T6 aluminum-lithium alloy.

[0077] Example 2

[0078] In terms of mass percentage, the base composition elements and contents of the cast aluminum-lithium alloy in this embodiment are: Li 2.5%, Cu 1.0%, Zr 0.15%, Mg 1.5%, Fe≤0.40%, and the balance is A1. The composite alloying scheme of this embodiment is to add 1.5% Si and 0.4% Er.

[0079] Alloy melting and casting :

[0080] Add pure aluminum, Al-50Cu alloy, Al-4Zr, Al-12Si and Al-20Er master alloy with good proportion into the crucible. The above alloy raw materials have been treated to remove surface oxide scale and anti-oxidation. Use a resistance furnace to raise the temperature to 750°C to 800°C for smelting. After all the materials are melted, slag is removed to form an alloy melt.

[0081] The temperature is lowered to 720°C to 730°C, and pure magnesium and pure lithium pellets wrapped in aluminum foil are pressed into the alloy melt in batches using a graphite cover under the protection of high-purity argon gas, with a burnout amount of 10% for pure magnesium and 20% for pure lithium. After the pure magnesium and pure lithium pellets diffuse into the melt and stabilize, C2Cl6 is wrapped in aluminum foil and pressed into the alloy melt, and degassing is performed using C2Cl6 at 740°C to 750°C until the melt does not emit black smoke and bubbles float out of the melt, and the amount of C2Cl6 is 0.6% of the total mass of the alloy;

[0082] The alloy melt was allowed to stand for 15 minutes and then cast at 720° C. to form a cast aluminum-lithium alloy blank;

[0083] During the above smelting and casting process, argon gas with a purity of 99.99% was used to protect the alloy melt. During the smelting and casting process, the argon gas flow rate was 1m 3 / h;

[0084] Solution and aging treatment :

[0085] In a box-type resistance furnace, a two-stage solution treatment process is used to perform solution treatment on the aluminum-lithium alloy blank obtained above, wherein the solution temperature of the first stage solution is 520°C, the solution time is 2 hours, and the solution temperature of the second stage solution is 540°C, the solution time is 14 hours;

[0086] The aluminum-lithium alloy blank after the solid solution treatment is quenched, and the quenching medium is water at room temperature, and the temperature is reduced from 540° C. to 25° C. as quickly as possible;

[0087] The aluminum-lithium alloy blank after the quenching treatment is placed in a salt bath furnace for double-stage aging treatment. The aging temperature of the first stage is 150°C and the duration is 12 h. The aging temperature of the second stage is 190°C and the duration is 8 h. It is then naturally cooled to room temperature to obtain a T6 aluminum-lithium alloy.

[0088] Example 3

[0089] In terms of mass percentage, the base composition elements and contents of the cast aluminum-lithium alloy in this embodiment are: Li 2.5%, Cu 1.0%, Zr 0.15%, Mg 1.5%, Fe≤0.40%, and the balance is A1. The composite alloying scheme of this embodiment is to add 1.8% Si, 0.10% Sc and 0.25% Er.

[0090] Alloy melting and casting :

[0091] Add pure aluminum, Al-50Cu alloy, Al-4Zr, Al-12Si, Al-10Sc and Al-20Er master alloy with good proportion into the crucible. The above alloy raw materials have been subjected to surface oxide skin removal and anti-oxidation treatment. The temperature is raised to 750°C to 800°C in a resistance furnace for smelting. After all the materials are melted, slag is removed to form an alloy melt.

[0092] The temperature is lowered to 720°C to 730°C, and pure magnesium and pure lithium pellets wrapped in aluminum foil are pressed into the alloy melt in batches using a graphite cover under the protection of high-purity argon gas, with a burnout amount of 10% for pure magnesium and 20% for pure lithium. After the pure magnesium and pure lithium pellets diffuse into the melt and stabilize, C2Cl6 is wrapped in aluminum foil and pressed into the alloy melt, and degassing is performed using C2Cl6 at 740°C to 750°C until the melt does not emit black smoke and bubbles float out of the melt, and the amount of C2Cl6 is 0.6% of the total mass of the alloy;

[0093] The alloy melt was allowed to stand for 15 minutes and then cast at 720° C. to form a cast aluminum-lithium alloy blank;

[0094] During the above smelting and casting process, argon gas with a purity of 99.99% was used to protect the alloy melt. During the smelting and casting process, the argon gas flow rate was 1m 3 / h;

[0095] Solution and aging treatment :

[0096] In a box-type resistance furnace, a two-stage solution treatment process is used to perform solution treatment on the aluminum-lithium alloy blank obtained above, wherein the solution temperature of the first stage solution treatment is 520°C and the solution time is 2 hours, and the solution temperature of the second stage solution treatment is 550°C and the solution time is 12 hours;

[0097] The aluminum-lithium alloy blank after the solution treatment is quenched, and the quenching medium is water at room temperature, and the temperature is reduced from 550° C. to 25° C. as quickly as possible;

[0098] The aluminum-lithium alloy billet after the quenching treatment is placed in a salt bath furnace for double-stage aging treatment. The aging temperature of the first stage is 150°C and the duration is 10 h. The aging temperature of the second stage is 190°C and the duration is 12 h. It is then naturally cooled to room temperature to obtain a T6 aluminum-lithium alloy.

[0099] Example 4

[0100] The difference between this embodiment and embodiment 1 is that:

[0101] In terms of mass percentage, the base composition elements and contents of the cast aluminum-lithium alloy in this embodiment are: Li 2.5%, Cu 1.0%, Zr 0.15%, Mg 1.8%, Fe ≤ 0.40%, and the balance is A1;

[0102] The composite microalloying scheme, the alloy melting and casting process, and the solution and aging treatment process are all consistent with those in Example 1.

[0103] Example 5

[0104] The difference between this embodiment and embodiment 1 is that:

[0105] In terms of mass percentage, the base composition elements and contents of the cast aluminum-lithium alloy in this embodiment are: Li 2.5%, Cu 1.0%, Zr 0.15%, Mg 0.5%, Fe ≤ 0.40%, and the balance is A1;

[0106] During the solution aging treatment, the second stage solution temperature was 560°C and the solution time was 10 h.

[0107] The composite microalloying scheme and the alloy melting and casting process are consistent with those in Example 1, and the other operations of solution treatment and aging treatment are also the same as those in Example 1.

[0108] Example 6

[0109] The difference between this embodiment and embodiment 2 is that:

[0110] The composite alloying scheme of this embodiment is to add 3.0% Si and 0.4% Er;

[0111] The reference elements and contents of the cast aluminum-lithium alloy, the alloy melting and casting process, and the solution and aging treatment process are all consistent with those in Example 2.

[0112] Example 7

[0113] The difference between this embodiment and embodiment 2 is that:

[0114] The composite alloying scheme of this embodiment is to add 1.5% Si and 0.55% Er;

[0115] During the solution aging treatment, the aging temperature of the first stage is 150℃ and the duration is 8h, and the aging temperature of the second stage is 175℃ and the duration is 48h;

[0116] The reference composition elements and contents of the cast aluminum-lithium alloy, and the alloy melting and casting process are consistent with those in Example 2, and the other operations of the solution treatment and aging treatment are also the same as those in Example 2.

[0117] Example 8

[0118] The difference between this embodiment and embodiment 3 is that:

[0119] The composite alloying scheme of this embodiment is to add 1.8% Si, 0.10% Sc and 0.10% Er;

[0120] The reference composition elements and contents of the cast aluminum-lithium alloy, the alloy melting and casting process, and the solution and aging treatment process are all consistent with those in Example 3.

[0121] Comparative Example 1

[0122] The difference between this comparative example and Example 2 is only that:

[0123] The composite alloying scheme of this comparative example is to add only 1.5% Si, without adding any rare earth elements including Sc and Er;

[0124] The reference elements and contents of the cast aluminum-lithium alloy, the alloy melting and casting process, and the solution and aging treatment process are all consistent with those in Example 2.

[0125] Comparative Example 2

[0126] The difference between this comparative example and Example 2 is only that:

[0127] The composite alloying scheme of this comparative example is to add only 0.4% Er and no Si element;

[0128] The reference elements and contents of the cast aluminum-lithium alloy, the alloy melting and casting process, and the solution and aging treatment process are all consistent with those in Example 2.

[0129] Comparative Example 3

[0130] The difference between this comparative example and Example 2 is only that:

[0131] The composite alloying scheme of this comparative example is to add 0.6% Si and 0.4% Er;

[0132] The reference elements and contents of the cast aluminum-lithium alloy, the alloy melting and casting process, and the solution and aging treatment process are all consistent with those in Example 2.

[0133] Comparative Example 4

[0134] The difference between this comparative example and Example 2 is only that:

[0135] In terms of mass percentage, the base composition elements and contents of the cast aluminum-lithium alloy in this embodiment are: Li 2.5%, Cu 1.0%, Zr 0.15%, Mg 0.4%, Fe≤0.40%, and the balance is A1; the composite alloying scheme of this embodiment is to add 0.4% Si and 0.4% Er;

[0136] The alloy melting and casting process as well as the solution and aging treatment process are consistent with Example 2.

[0137] [Tissue morphology characterization]

[0138] Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used to characterize the microstructure of the as-cast and T6 state Al-Li alloy samples.

[0139] The cast aluminum-lithium alloys ( Figure 1 ) and T6 aluminum-lithium alloy ( Figure 2 ) were characterized by:

[0140] Depend on Figure 1 It can be seen that rare earth element alloying can effectively refine the alloy grains. At the same time, a large number of letter-shaped AlSiLi intergranular phases distributed nearly continuously or discontinuously along the grain boundaries appear in the cast structure of the alloy. With the increase of Si content, the volume fraction of the letter-shaped AlSiLi phase also increases.

[0141] Depend on Figure 2It can be seen that after the alloy is subjected to double-stage solid solution and double-stage aging treatment, a part of the letter-shaped AlSiLi intergranular phase distributed nearly continuously or discontinuously along the grain boundary dissolves back into the matrix, and the edge of the residual second phase (i.e., the undissolved AlSiLi intergranular phase) becomes smoother.

[0142] The microstructure morphology of the T6 aluminum-lithium alloy in Examples 1 to 3 was further characterized by TEM:

[0143] Depend on Figure 3 It can be seen that with the increase of the mass content of Si element in the alloy composition, the morphology of the AlSiLi intergranular phase observed under TEM changes from rod-shaped to letter-shaped; at the same time, after solution aging (T6) heat treatment, the AlSiLi intergranular phase in the alloy presents an arc-shaped edge.

[0144] Depend on Figure 4 It can be seen that the AlSiLi intergranular phase is nearly continuously distributed at the grain boundaries of the T6 alloy in Example 3.

[0145] [Mechanical properties test]

[0146] The T6 aluminum-lithium alloys in the above examples and comparative examples were subjected to tensile tests at room temperature (25°C), 200°C, and 300°C, respectively. The specific operation of the room temperature tensile test is carried out in accordance with GB / T228.1-2021 "Metallic Material Tensile Test Part 1: Room Temperature Test Method", and the specific operation of the high temperature tensile test is carried out in accordance with GB / T 4338-2006 "Metallic Material High Temperature Tensile Test Method". When testing the high temperature mechanical properties, the alloy sample is first kept warm for half an hour to ensure the full dissolution of the metastable phase in the alloy, and then the tensile test is carried out.

[0147] The test temperatures as well as the yield strength, tensile strength, and elongation measured by room temperature / high temperature tensile tests are recorded in Table 1.

[0148] Table 1

[0149]

[0150]

[0151] Compared with the test results of the comparative examples, the comprehensive mechanical properties of the above embodiments at room temperature and high temperature are better, and improved room temperature / high temperature toughening effects are achieved. Comparative Example 1 does not add rare earth elements, and the yield strength and tensile strength at room temperature are significantly lower. Comparative Example 2 does not add Si elements, and the mass percentage of Si elements in Comparative Example 3 is less than 0.8%, and the AlSiLi intergranular strengthening phase cannot be formed or the intergranular strengthening phase is insufficient, and significant softening instability occurs at high temperatures.

[0152] A comprehensive analysis of the embodiments shows that: when the mass fraction ratio of Mg to Si is in the range of 0.83 to 1.88, the strength, plasticity and ductility at room temperature and high temperature are more balanced, with relatively higher tensile strength and yield strength at room temperature, and stronger ability to resist softening deformation at high temperature. In Example 4, Mg / Si is 2.25, which tends to precipitate larger sized precipitation strengthening phases from the alloy matrix, affecting the strength at room temperature and 200°C. In Example 6, the mass percentage of Si element is 3.0%, and Mg / Si is only 0.50, which easily forms a larger AlSiLi intergranular phase, resulting in relatively low strength-plasticity at room temperature and high temperature.

[0153] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A cast aluminum-lithium alloy, characterized in that: Calculated by mass percentage, the cast aluminum-lithium alloy includes: 2.0% to 3.0% Li, 0.8% to 1.2% Cu, 0.1% to 0.2% Zr, 0.5% to 1.8% Mg, 0.8% to 3.0% Si, 0.15% to 0.55% rare earth elements, ≤0.40% Fe, and the balance is Al; the rare earth elements include Sc and / or Er.

2. The cast aluminum-lithium alloy according to claim 1, characterized in that: Based on the total weight of the cast aluminum-lithium alloy, the rare earth elements include 0.15% to 0.30% Sc, 0.35% to 0.55% Er, or a combination of Sc and Er, and when the rare earth elements include a combination of Sc and Er, the mass percentage of Sc is 0.10% to 0.15%, and the mass percentage of Er is 0.15% to 0.25%.

3. The cast aluminum-lithium alloy according to claim 1 or 2, characterized in that: The mass fraction ratio Mg / Si of the Mg element to the Si element in the cast aluminum-lithium alloy is 0.63-1.

88.

4. The cast aluminum-lithium alloy according to any one of claims 1 to 3, characterized in that: The cast aluminum-lithium alloy has a rod-shaped Mg2Si precipitate phase on the α-Al matrix phase.

5. The cast aluminum-lithium alloy according to any one of claims 1 to 4, characterized in that: The cast aluminum-lithium alloy has an AlSiLi intermetallic compound phase distributed along the grain boundary in a discontinuous or nearly continuous manner.

6. The cast aluminum-lithium alloy according to any one of claims 1 to 5, characterized in that: The cast aluminum-lithium alloy meets one or more of the following characteristics: (1) At 25°C, the yield strength is 286-326 MPa, the tensile strength is 314-389 MPa and / or the elongation is 4.2%-14.7%; (2) at 200°C, the yield strength is 211 to 250 MPa, the tensile strength is 223 to 297 MPa and / or the elongation is 7.4% to 13.9%; (3) At 300°C, the yield strength is 109 to 148 MPa, the tensile strength is 115 to 159 MPa and / or the elongation is 12.4% to 17.3%.

7. A method for preparing a cast aluminum-lithium alloy, comprising: Step 1, smelting alloy raw materials to obtain aluminum liquid, and pouring the aluminum liquid to form an aluminum-lithium alloy blank, wherein the alloy raw materials include, by mass percentage: 2.0% to 3.0% Li, 0.8% to 1.2% Cu, 0.1% to 0.2% Zr, 0.5% to 1.8% Mg, 0.8% to 3.0% Si, 0.15% to 0.55% rare earth elements, ≤0.40% Fe, and the balance is Al; the rare earth elements include Sc and / or Er; Step 2: The aluminum-lithium alloy blank is subjected to a double-stage solution treatment, a quenching treatment and a double-stage aging treatment in sequence to obtain the cast aluminum-lithium alloy.

8. The preparation method according to claim 7, characterized in that: The double-stage solution treatment includes a first-stage solution treatment and a second-stage solution treatment performed sequentially, wherein the solution temperature T s1 500℃~520℃, solution time t s1 The second stage solid solution temperature T s2 540℃~560℃, solution time t s2 It is 10 to 16 hours.

9. The preparation method according to claim 7 or 8, characterized in that: The two-stage aging treatment includes a first-stage aging and a second-stage aging performed sequentially, and the aging temperature T of the first-stage aging is a1 150℃±3℃, aging time t a1 The aging temperature of the second stage aging is T a2 175℃~190℃, aging time t a2 8 to 48 hours.

10. The preparation method according to any one of claims 7 to 9, characterized in that: The step one comprises: Melting pure aluminum and an aluminum-based master alloy containing alloying elements at 750° C. to 800° C. to form an alloy melt, wherein the alloying elements include one or more of Cu, Zr, Si, and rare earth elements, and the rare earth elements include Sc and / or Er; Lowering the temperature to 720° C. to 730° C., and pressing pure magnesium wrapped in aluminum foil and pure lithium wrapped in aluminum foil into the alloy melt under a protective atmosphere, wherein the protective atmosphere may be nitrogen and / or argon; The temperature is adjusted to 740° C. to 750° C., a degassing agent is used to degas the alloy melt, and the alloy melt is allowed to stand to obtain aluminum liquid; The aluminum liquid is poured at 720°C±5°C to form an aluminum-lithium alloy blank.

11. The preparation method according to any one of claims 7 to 10, characterized in that: The entire process of step 1 is carried out under a protective gas atmosphere, wherein the protective gas may be argon gas, and may further be argon gas with a purity of not less than 99.99% and a flow rate of 0.5 m / s. 3 / h~1.5m 3 / h of argon.

12. The preparation method according to any one of claims 7 to 11, characterized in that: The step 1 satisfies one or more of the following conditions: 1) The degassing agent is selected from any one or more of C2Cl6, CCl4, and Mg3N2, preferably C2Cl6, and more preferably, C2Cl6 is 0.45% to 0.8% of the total mass of the alloy raw material; 2) The standing time is 10 to 15 minutes.

13. The preparation method according to any one of claims 7 to 12, characterized in that: The preparation method further comprises pre-treating the alloy raw material, wherein the pre-treating the alloy raw material comprises: removing surface oxide scale and performing anti-oxidation treatment on pure aluminum and aluminum-based master alloy containing alloying elements.

14. The preparation method according to any one of claims 7 to 13, characterized in that: During the quenching treatment, the temperature is rapidly reduced from 540° C. to 560° C. to 25° C., and the quenching medium is preferably salt water or water at room temperature.

15. A heat-resistant lightweight structural part, comprising an aluminum-lithium alloy, characterized in that: The aluminum-lithium alloy is the cast aluminum-lithium alloy according to any one of claims 1 to 6, or the aluminum-lithium alloy is obtained by the preparation method according to any one of claims 7 to 14.